A latest Pleistocene and Holocene composite tephrostratigraphic framework for northeastern North America. (15th November 2021) - Jensen, Britta J.L.; Davies, Lauren J.; Nolan, Connor; Pyne-O'Donnell, Sean; Monteath, Alistair J.; Ponomareva, Vera; Portnyagin, Maxim; Booth, Robert; Bursik, Marcus; Cook, Eliza; Plunkett, Gill; Vallance, James W.; et al.
Abstract: Lakes and bogs in northeastern North America preserve tephra deposits sourced from multiple volcanic systems in the Northern Hemisphere. However, most studies of these deposits focus on specific Holocene intervals and the latest Pleistocene, providing snapshots rather than a full picture. We combine new data with previous work, supplemented by a broad review of the characteristics and ages of potential source regions and volcanoes, to develop the first composite tephrostratigraphic framework covering the last ∼14, 000 years for this region. We report new cryptotephra records from three ombrotrophic peat bogs—Irwin Smith (Michigan), Bloomingdale (New York), and Sidney Bog (Maine)—as well as new analyses and age models from previously reported sites, Nordan's Pond Bog (Newfoundland) and Thin-Ice Pond (Nova Scotia). A new tephra (Iliinsky) from the NGRIP and GRIP ice cores is also presented as it can be correlated to new data from these terrestrial records and helps validate radiocarbon age models. We identify 21 new tephra in addition to the 15 already known, several of which cover the entire region – the White River Ash east, Newberry Pumice, Ruppert (NDN-230), and Mazama. For the first time we find Mount St. Helens Yn (ca. 3660 cal yr BP) and a set P tephra (∼3000–2550 cal yr BP), and confirm the presence of Jala Pumice from Volcan Ceboruco, Mexico, and KS1 from Ksudach volcano, Kamchatka. We describe new "ultra-distal" tephra, including the early Holocene KS2 eruption, and propose correlations to volcanoes Iliinsky and Shiveluch of Kamchatka, and Ushishir of the Kurile Islands. Not all of these tephra represent large eruptions, with several plausible correlations to sub-Plinian events. Using Bayesian age-modeling, we present new age estimates for the newly described tephra, for tephra with previously poor age control, and for several proximal correlatives. Overall, we demonstrate northeastern North America's importance for providing transcontinental linkages between paleoenvironmental records and providing insights into ash distribution from different styles and sizes of eruptions. Highlights: Tephra are abundant in NE North America, with 36 unique units deposited between ∼14, 000 and the present day. Source volcanoes are in the Cascades, Alaska, Kamchatka, Kuriles and potentially Japan. Updated Bayesian modelled ages are presented for key proximal correlative eruptions and newly described tephra. The tephra link paleoenvironmental records from this region to the Far East, Greenland and Europe. Correlated source eruption volumes vary widely; this alone cannot explain recorded ash distribution trends.